2012
DOI: 10.5334/jeps.ao
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to pets and interpersonal relationships: Can a four-legged friend replace a two-legged one?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 27 publications
4
22
1
8
Order By: Relevance
“…These findings are in line with previous research showing that stronger human-animal relationships are associated with increased reports of psychopathological symptoms [63][64][65][66]. However, they are inconsistent with findings that suggest either no association between living with a companion animal and well-being [67,68] or findings linking strong human-animal bonds with positive mental health outcomes [36]. One hypothesis -brought up by Müllersdorf et al [69] -that may explain poorer mental health reported by pet owners strongly attached to their pet is that individuals who are predisposed to experience mental health problems are more likely to obtain a pet and bond to the pet strongly as some kind of self-help strategy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in line with previous research showing that stronger human-animal relationships are associated with increased reports of psychopathological symptoms [63][64][65][66]. However, they are inconsistent with findings that suggest either no association between living with a companion animal and well-being [67,68] or findings linking strong human-animal bonds with positive mental health outcomes [36]. One hypothesis -brought up by Müllersdorf et al [69] -that may explain poorer mental health reported by pet owners strongly attached to their pet is that individuals who are predisposed to experience mental health problems are more likely to obtain a pet and bond to the pet strongly as some kind of self-help strategy.…”
Section: Discussionsupporting
confidence: 83%
“…However, these studies have yielded inconsistent results. While some found a substantial relationship between strong attachment to pets and lower degree of loneliness as well as depression [34,35], others did not find any association or even positive relationships between attachment to pets and loneliness as well as depression [36]. These inconsistent findings indicate that a stronger attachment to pets does not necessarily result in lower levels of psychopathological symptoms.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, in our study the length of tortoise ownership is generally less than three years. This is very short when considering the long lifespan of tortoise species, and much shorter than for other pets like dogs or cats in Europe [61], but is in line with that of other wild pets, high percentages of which end up being abandoned or in animal care centers owing to their overly demanding requirements [62]. Moreover, there is almost a complete absence of tortoise veterinary care in Rabat and its surroundings, which contrasts with the frequent care of other domestic pets like cats, dogs or rabbits in, for example, North America [63].…”
Section: Animal Preference Welfare and Pet Knowledgementioning
confidence: 99%
“…O fato de ter sido observada diferença significativa na AE apenas nos voluntários que convivem com cães pode estar relacionado ao fato de que esta espécie, geralmente, apresenta alto nível de apego com o tutor, estando esta variável diretamente proporcional à qualidade de vida do tutor (WHITE et al, 2017). Adicionalmente, foi observado em estudo prévio (SMOLKOVIC et al, 2012) que o apego do tutor com cão é maior que com outras espécies. Além disso, no presente estudo houve uma maior incidência de indivíduos que relataram conviver com cães, em comparação com outras espécies.…”
Section: Períodounclassified
“…É importante salientar que a raça foi definida de acordo com a consideração dos próprios participantes, não tendo sido confirmada oficialmente esta classificação através de pedigree no presente estudo. Segundo Smolkovic et al (2012), é possível que o apego do tutor com o animal seja maior quando o pet possui pedigree, devido a fatores como investimento para compra e escolha da raça. Entretanto, os resultados do presente estudo com relação ao pedigree do animal demonstram que, independente da raça, o convívio com pet promove melhorias na AE dos tutores.…”
Section: Períodounclassified